[tex] - 15 + 9 + ( - 9) + 15 = \\ - 15 + 9 - 9 + 15 = 0[/tex]
[tex] -3 5 + ( - 19) + 28 + 19 = \\ - 35 - 19 + 28 + 19 = \\ - 35 + 28 = - 7[/tex]
[tex]2.47 + ( - 2.11) + ( - 7.89) + 6.53 = \\ 2.47 - 2.11 - 7.89 + 6.53 = \\ 9 - 10 = - 1[/tex]
[tex]1.9 + ( - 3) + ( - 1.9) + 9 + ( - 2) = \\ 1.9 - 3 - 1.9 + 9 - 2 = 9 - 3 - 2 = \\ 9 - 5 = 4[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex] - 15 + 9 + ( - 9) + 15 = \\ - 15 + 9 - 9 + 15 = 0[/tex]
[tex] -3 5 + ( - 19) + 28 + 19 = \\ - 35 - 19 + 28 + 19 = \\ - 35 + 28 = - 7[/tex]
[tex]2.47 + ( - 2.11) + ( - 7.89) + 6.53 = \\ 2.47 - 2.11 - 7.89 + 6.53 = \\ 9 - 10 = - 1[/tex]
[tex]1.9 + ( - 3) + ( - 1.9) + 9 + ( - 2) = \\ 1.9 - 3 - 1.9 + 9 - 2 = 9 - 3 - 2 = \\ 9 - 5 = 4[/tex]